2019
DOI: 10.18502/jfrh.v13i3.2131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Vitamin D Level and Ectopic Pregnancy: A Case-control Study

Abstract: Objective: To compare the difference in Vitamin D level between women with ectopic pregnancy and control group. Materials and methods: In the present case-control study, 150 patients with ectopic pregnancy were included as case group and 150 women with normal pregnancy as a control group. Then, serum vitamin D levels were measured in both groups and they were then compared with each other. P value less than 0.05 was considered statistically significant. Results: The mean age in ectopic pregnancy gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[ 14 ] In the present study that was carried out to investigate the association of serum vitamin D levels with the incidence of ectopic pregnancy, it was revealed that the level of vitamin D in healthy pregnant women was significantly higher than the women with ectopic pregnancy, which is consistent with the result of the Sahhaf et al . [ 12 ] study. Besides, Bahat et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 14 ] In the present study that was carried out to investigate the association of serum vitamin D levels with the incidence of ectopic pregnancy, it was revealed that the level of vitamin D in healthy pregnant women was significantly higher than the women with ectopic pregnancy, which is consistent with the result of the Sahhaf et al . [ 12 ] study. Besides, Bahat et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] The results achieved from studies have showed that there is a direct relationship between insufficient levels of vitamin D in the blood and the incidence of ectopic pregnancy. [ 11 12 ] Therefore, because of the limited number of studies conducted on this issue on the one hand, and the widespread of vitamin D deficiency, especially among Iranian women on the other hand, in the present study, the association of serum vitamin D levels and ectopic pregnancy during the first trimester was evaluated.…”
Section: Introductionmentioning
confidence: 99%